The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/obr.12217
|View full text |Cite
|
Sign up to set email alerts
|

Does weight loss in overweight or obese women improve fertility treatment outcomes? A systematic review

Abstract: SummaryThis systematic review assessed the effect of weight loss in overweight and/or obese women undergoing assisted reproductive technology (ART) on their subsequent pregnancy outcome. Weight losses achieved by diet and lifestyle changes, very--low--energy diets, non--surgical medical interventions and bariatric surgery translated into significantly increased pregnancy rates and/or live birth in overweight and/or obese women undergoing ART in 8 of the 11 studies reviewed. In addition, regularization of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 62 publications
4
74
0
2
Order By: Relevance
“…One small study suggested that there was no improvement in overall sexual function after LAGB in males and that erectile index and orgasmic function worsened when adjusted for time (164). The evidence supporting an effect of weight loss on the management of fertility issues is of relative low quality, but the overall results suggest a benefit (192). Studies to evaluate the effect of bariatric surgery on male fertility are needed (139).…”
Section: Effect Of Sustained Weight Loss On Fertility/pregnancymentioning
confidence: 95%
“…One small study suggested that there was no improvement in overall sexual function after LAGB in males and that erectile index and orgasmic function worsened when adjusted for time (164). The evidence supporting an effect of weight loss on the management of fertility issues is of relative low quality, but the overall results suggest a benefit (192). Studies to evaluate the effect of bariatric surgery on male fertility are needed (139).…”
Section: Effect Of Sustained Weight Loss On Fertility/pregnancymentioning
confidence: 95%
“…Preconception weight loss in obese women is also important to reduce morbidity from anesthesia-related surgical procedures, such as oocyte retrieval (124). To date, however, there is no strong evidence that preconception weight loss in women improves IVF-related pregnancy outcome (125), and the data are less clear in men. Nevertheless, weight loss is assumed to benefit fertility as it does for diabetes and CVD.…”
Section: Management Lifestyle Modificationmentioning
confidence: 99%
“…Several studies demonstrate the benefit of weight loss as part of a structured weight loss program upon the chance of conception for overweight women, and also as part of their IVF treatment (61,314). In a systematic review of 11 stud-ies that met the search criteria weight loss on the outcome of subsequent IVF treatment, losing weight by either diet and lifestyle changes (7 studies), nonsurgical medical interventions (1 study), or bariatric surgery (2 studies) led to a significant increase in the natural conception rate, an increase in the number of embryos available for transfer as well as the subsequent pregnancy rate, and a decrease in the miscarriage rate (314).…”
Section: Obesitymentioning
confidence: 99%
“…In a systematic review of 11 stud-ies that met the search criteria weight loss on the outcome of subsequent IVF treatment, losing weight by either diet and lifestyle changes (7 studies), nonsurgical medical interventions (1 study), or bariatric surgery (2 studies) led to a significant increase in the natural conception rate, an increase in the number of embryos available for transfer as well as the subsequent pregnancy rate, and a decrease in the miscarriage rate (314). Due to the difficulty in completing such studies, the overall quality of the studies was reported as weak, although all interventions led to significant improvements in pregnancy or live birth rates in overweight or obese women, with several studies reporting an improvement in spontaneous pregnancy rates.…”
Section: Obesitymentioning
confidence: 99%